“WHAT MUST BE, MUST BE” („WAS SEIN MUSS, MUSS SEIN“) - Wolfgang Mieder; Andreas Nolte (Proverbium, 2021)
In our 526-page book „Ein Schwert hält das andere in der Scheide“ Otto von Bismarck's Proverbial Rhetoric (2018), we have shown the extensive use of proverbs and proverbial sayings by Prince Otto von Bismarck (1815-1898). As Prime Minister of Prussia and German Chancellor, he achieved a tremendous amount in domestic and foreign policy as a Realpolitiker, and his power of language, characterized by proverbs, served him well in rhetoric. This short version of our extensive inventory only deals with selected proverbs, excluding numerous sayings. First of all, it's about proverbs in personal and political discourse, for which the saying "Many enemies, much honor" used by Bismarck may serve as a guiding principle. This is followed by a consideration of some politically applied Bible proverbs, with the proverb “When the heart is full, the mouth overflows” (Deuteronomy 8:3; Matt. 4:4) turns out to be a kind of leitmotif. We then deal with “Loan Proverbs of a Multilingual Politician,” where it emerges that Bismarck repeatedly prefers the French version “L’homme propose, Dieu dispose” of the German proverb “Man thinks, God directs.” In addition, as a trained lawyer, he also uses Latin proverbs.